Impact of the Australian marriage equality postal survey and debate on psychological distress among lesbian, gay, bisexual, transgender, intersex and queer/questioning people and allies - Saan Ecker; Ellen D.b. Riggle; Sharon S. Rostosky; Joanne M. Byrnes (Australian Journal of Psychology, 2019)
Objective In August 2017, the Australian Government announced a voluntary, non‐binding postal survey to seek opinion on the legal recognition of same‐sex marriage. The government encouraged public debate on the issue. This study sought to identify impacts of the Australian postal survey and associated marriage equality debate on psychological distress experienced by lesbian, gay, bisexual, transgender, intersex, and queer/questioning (LGBTIQ) people and their allies. Method LGBTIQ identified people (n = 5,742) and people who identified as allies of LGBTIQ (n = 1,648) were recruited via social media to complete an online questionnaire administered during the survey and debate period. Participants completed demographic items, and measures of debate‐related stress, prior experiences of depression, stress and anxiety, prior stressful life events, and psychological distress. Results LGBTIQ people and allies reported high levels of debate‐related stress, which was moderately and positively correlated with psychological distress. Comparison of means and correlation coefficients, and a preliminary multiple regression model suggested that LGBTIQ and allies experienced debate‐related stress differently. Therefore, separate hierarchical regressions were performed for the groups. Debate‐related stress accounted for unique variance in psychological distress in each group after accounting for prior life stress, prior psychological distress, and demographic variables. Conclusions Debate‐related stress predicted psychological distress for both LGBTIQ people and allies. Findings suggest that the marriage equality debate represented an acute external minority stress event that had measurable negative impacts on mental health of LGBTIQ people and their allies.